Admission Hemoglobin Associated with Increased Mortality in Hip Fracture Surgical Patients: An Observational Study - Ana Šarić Jadrijev; Ana Bego; Borna Lojpur; Dino Poljak; Marija Žaja; Jakov Matas; Božen Pivalica; Sanda Stojanović Stipić; Vesna Čapkun; Katarina Vukojević; Merica Glavina Durdov; Andre Bratanić (Biomedicines)
In hip fracture patients, who are mostly elderly, preexisting anemia can be worsened when combined with trauma and surgery. To this date, there is no unequivocal approach about transfusion thresholds. We analyzed hemoglobin (Hb) and hematocrit (Hct) levels at three time points in surgical patients with proximal femoral fractures (PFF) to see which levels were triggers for transfusions and whether transfusions were related to mortality after hospital discharge. A total of 956 patients were operated on from 1 January 2021 to 31 December 2022 at the University Hospital of Split and included in the study. There were more women (74%); 47% patients had admission Hb < 120 g/L. Transfusion was given preoperatively to 88, intraoperatively to 74 and postoperatively to 309 patients. Transfusion thresholds were as follows: Hb 84 g/L preoperatively, 99 intraoperatively and 83 postoperatively. After hospital discharge, 10.79% of patients died within the 1st month and 23% within 6 months. In the group of non-survivors, 60% of patients had admission Hb ≤ 117 g/L and the proportion of patients transfused preoperatively was two times higher. Preoperative transfusion thresholds could be set to higher levels for patients with surgically treated PFF. However, that could increase mortality even more. Further investigation is necessary.